Maintenance of Efficacy and Safety of Ustekinumab Through One Year in a Phase II Multicenter, Prospective, Randomized, Double‐Blind, Placebo‐Controlled Crossover Trial of Patients With Active Systemic Lupus Erythematosus. Issue 5 (1st April 2020) - van Vollenhoven, Ronald F.; Hahn, Bevra H.; Tsokos, George C.; Lipsky, Peter; Fei, Kaiyin; Gordon, Robert M.; Gregan, Irene; Lo, Kim Hung; Chevrier, Marc; Rose, Shawn
Abstract : Objective: To evaluate the efficacy and safety of ustekinumab through 1 year in a phase II trial in patients with systemic lupus erythematosus (SLE). Methods: Eligible patients were diagnosed as having clinically active SLE (based on Systemic Lupus International Collaborating Clinics criteria), despite standard background therapy. Active disease was defined by an SLE Disease Activity Index 2000 (SLEDAI‐2K) score of ≥6 as well as having ≥1 British Isles Lupus Assessment Group (BILAG) A organ domain score and/or ≥2 BILAG B organ domain scores present at screening. Patients (n = 102) were randomized (3:2) to receive either ustekinumab (~6 mg/kg of single intravenous infusion at week 0, then 90‐mg subcutaneous injections every 8 weeks beginning at week 8) or a matching placebo added to standard therapy. At week 24, the placebo group crossed over to receive a subcutaneous 90‐mg dose of ustekinumab every 8 weeks, and the original ustekinumab group continued to receive therapy through week 40. Maintenance of efficacy was assessed using the SLEDAI‐2K, the SLE Responder Index 4 (SRI‐4), physician global assessment, and mucocutaneous and joint disease measures in a modified intent‐to‐treat population. Results: SRI‐4 response rates were significantly greater in the ustekinumab group (62%) versus the placebo group (33%) in the week 24 primary end point analysis ( P = 0.006) and were maintained at week 48 (63.3%) in the ustekinumab group. In the ustekinumab group, response rates across other disease measures were also maintained through week 48. Among patients in the placebo group who crossed over to ustekinumab treatment (n = 33), increased response rates across efficacy measures were noted. Among all ustekinumab‐treated patients, 81.7% had ≥1 adverse event (AE), and 15.1% had ≥1 serious AE through week 56. No deaths, malignancies, opportunistic infections, or tuberculosis cases were observed. Conclusion: Ustekinumab provided sustained clinical benefit in patients with SLE through 1 year, with a safety profile consistent with other indications.